Perilaku Prososial Remaja di Tinjau dari Kecerdasan Emosional dan Religiusitas - Oktin Genisa; Triantoro Safaria; Aulia Aulia (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
This study aims to determine the effect of emotional intelligence and religiosity on prosocial behavior in adolescents. The approach used in this research is a quantitative approach with a cross sectional study design. The population in this study were adolescents aged 15-18 years, with the total number of Indonesian adolescents aged 22,312.6. The area of distribution of research data was carried out in several provinces, including West Sumatra, South Sumatra, North Sumatra, Jambi, Bengkulu, West Java, Central Java, East Java, Yogyakarta, NTB and NTT. The sampling technique used in this study is the quota sampling technique. The sample in this study amounted to 384 adolescents in Indonesia. The data collection tool was carried out using a scale of emotional intelligence, religiosity and prosocial behavior. The data analysis technique used is multiple regression. The data results show the value of R = 0.984 and F = 5941.766 with a significant level of p 0.01. The effective contribution (R Square) produced is R2 = 0.969, which means that simultaneously emotional intelligence and religiosity contribute 96.9% to prosocial behavior. It can be concluded that emotional intelligence and religiosity have a significant influence on adolescent prosocial behavior, meaning that adolescents who have high emotional intelligence and religiosity have high social behavior.